Формування та ведення національної базової колекції соняшнику в Україні - Рябчун, В.К.; Кривошеєва, О.В.; Ведмедева, К.В. (Фактори експериментальної еволюції організмів, 2008)
Изложены результаты формирования базовой коллекции подсолнечника по
морфологическим, биологическим и другим хозяйственным признакам в условиях
Украины. Выделены источники с высоким уровнем ценных хозяйственных признаков,
доноры морфологичных признаков, которые могут быть использованы как исходный
материал в селекции сортов и гибридов. There have been presented the data on the studies of the sunflower genepool as to
morphological, biological, economical traits and with resistance to pathogens causing major
diseases of sunflower under the conditions of Ukraine. There have been identified the sources
possessing a high level of the economical traits, of morpholoqical marker traits, which can be
used as the initial material for breeding varieties and hybrids.